Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(ĐKXĐ:a>1\)
\(P=\left(\frac{\sqrt{a}+2}{a+2\sqrt{a}+1}-\frac{\sqrt{a}-2}{a-1}\right)\cdot\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(\Leftrightarrow P=\left(\frac{\sqrt{a}+2}{\left(\sqrt{a}+1\right)^2}-\frac{\sqrt{a}-2}{\left(\sqrt{a}-1\right)\left(\sqrt{a}+1\right)}\right)\cdot\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(\Leftrightarrow P=\frac{\left(\sqrt{a}+2\right)\left(\sqrt{a}-1\right)-\left(\sqrt{a}-2\right)\left(\sqrt{a}+1\right)}{\left(\sqrt{a}+1\right)^2\left(\sqrt{a}-1\right)}\cdot\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(\Leftrightarrow P=\frac{a+\sqrt{a}-2-a+\sqrt{a}+2}{\sqrt{a}\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}\)
\(\Leftrightarrow P=\frac{2\sqrt{a}}{\sqrt{a}\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}\)
\(\Leftrightarrow P=\frac{2}{a-1}\)
\(ĐKXĐ:\hept{\begin{cases}a>0\\a\ne1\end{cases}}\)
Ta có :
\(P=\left(\frac{\sqrt{a}+2}{a+2\sqrt{a}+1}-\frac{\sqrt{a}-2}{a-1}\right).\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(=\left(\frac{\sqrt{a}+2}{\left(\sqrt{a}+1\right)^2}-\frac{\sqrt{a}-2}{\left(\sqrt{a}-1\right)\left(\sqrt{a}+1\right)}\right).\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(=\left(\frac{\left(\sqrt{a}+2\right)\left(\sqrt{a}-1\right)-\left(\sqrt{a}-2\right)\left(\sqrt{a}+1\right)}{\left(\sqrt{a}+1\right)^2\left(\sqrt{a}-1\right)}\right).\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(=\left(\frac{\left(a+\sqrt{a}-2\right)-\left(a-\sqrt{a}-2\right)}{\left(\sqrt{a}+1\right)^2\left(\sqrt{a}-1\right)}\right).\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(=\frac{2\sqrt{a}}{\left(\sqrt{a}+1\right)^2\left(\sqrt{a}-1\right)}.\frac{\sqrt{a}+1}{\sqrt{a}}\)
\(=\frac{2}{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}\)
\(=\frac{2}{a-1}\)
Vậy \(P=\frac{2}{a-1}\left(a>0;a\ne1\right)\)
\(P=\left(\frac{1}{\sqrt{a}-1}-\frac{1}{\sqrt{a}}\right):\left(\frac{\sqrt{a}+1}{\sqrt{a}-2}-\frac{\sqrt{a}+2}{\sqrt{a}-1}\right)\)
\(=\frac{\sqrt{a}-\sqrt{a}+1}{\sqrt{a}\cdot\left(\sqrt{a}-1\right)}:\frac{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)-\left(\sqrt{a}+2\right)\left(\sqrt{a}-2\right)}{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}\)
\(=\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}\cdot\frac{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}{a-1-a+4}\)
\(=\frac{\sqrt{a}-2}{3\sqrt{a}}\)
1.
ĐK \(a\ge0;a\ne1\)
Ta có \(A=\left(\frac{\sqrt{a}+1}{\sqrt{a}-1}-\frac{\sqrt{a}-1}{\sqrt{a}+1}+4\sqrt{a}\right).\left(\sqrt{a}-\frac{1}{\sqrt{a}}\right)\)
\(=\frac{\left(\sqrt{a}+1\right)^2-\left(\sqrt{a}-1\right)^2+4\sqrt{a}\left(a-1\right)}{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}.\frac{a-1}{\sqrt{a}}\)
\(=\frac{a+2\sqrt{a}+1-a+2\sqrt{a}-1+4a\sqrt{a}-4\sqrt{a}}{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}.\frac{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}{\sqrt{a}}\)
\(=\frac{4a\sqrt{a}}{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}.\frac{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}{\sqrt{a}}=4a\)
2. Với \(a=\frac{\sqrt{6}}{2+\sqrt{6}}\Rightarrow A=\frac{4\sqrt{6}}{2+\sqrt{6}}\)
Để \(\sqrt{A}>A\Rightarrow\sqrt{4a}>4a\Rightarrow2\sqrt{a}-4a>0\Rightarrow2\sqrt{a}\left(1-2\sqrt{a}\right)>0\)
\(\Rightarrow\hept{\begin{cases}\sqrt{a}>0\\1-2\sqrt{a}>0\end{cases}\Rightarrow\hept{\begin{cases}a>0\\a>\frac{1}{4}\end{cases}\Rightarrow}a>\frac{1}{4}}\)
Vậy để \(\sqrt{A}>A\)thì \(a>\frac{1}{4};a\ne1\)
a) \(\sqrt{\left(1-\sqrt{5}\right)^2}-\sqrt{\left(3-\sqrt{5}\right)^2}=\left(\sqrt{5}-1\right)-\left(3-\sqrt{5}\right)=2\sqrt{5}-4\)
b) \(\frac{a-2\sqrt{a}+1}{\sqrt{a}-1}=\frac{\left(\sqrt{a}-1\right)^2}{\sqrt{a}-1}=\sqrt{a}-1\) ( \(a\ge0\ne1\))
c) \(\frac{a+\sqrt{a}}{a}=\frac{\sqrt{a}\left(\sqrt{a}+1\right)}{\sqrt{a}.\sqrt{a}}=\frac{\sqrt{a}+1}{\sqrt{a}}=1+\frac{1}{\sqrt{a}}\)(\(a>0\))
d) \(\frac{3+\sqrt{3}}{1+\sqrt{3}}=\frac{\sqrt{3}\left(\sqrt{3}+1\right)}{\sqrt{3}+1}=\sqrt{3}\)
a) \(A=\left(\frac{1}{a-\sqrt{a}}+\frac{1}{\sqrt{a}-1}\right):\frac{\sqrt{a}+1}{a-2\sqrt{a}+1}\left(a>0;a\ne1\right)\)
\(=\left[\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}+\frac{1}{\sqrt{a}-1}\right]:\frac{\sqrt{a}+1}{\left(\sqrt{a}-1\right)^2}\)
\(=\frac{1+\sqrt{a}}{\sqrt{a}\left(\sqrt{a}-1\right)}\cdot\frac{\left(\sqrt{a}-1\right)^2}{\sqrt{a}+1}\)
\(=\frac{\sqrt{a}-1}{\sqrt{a}}\)
b) Để \(A=\frac{1}{2}\)
\(\Leftrightarrow\frac{\sqrt{a}-1}{\sqrt{a}}=\frac{1}{2}\)
\(\Leftrightarrow2\sqrt{a}-2=\sqrt{a}\)
\(\Leftrightarrow\sqrt{a}=2\Leftrightarrow a=4\left(tm\right)\)
\(M=\left(\frac{a-2\sqrt{a}+1}{a+1}\right):\left[\frac{1}{\sqrt{a}-1}-\frac{2\sqrt{a}}{\sqrt{a}\left(a+1\right)-\left(a+1\right)}\right]\)
\(M=\left[\frac{\left(\sqrt{a}-1\right)^2}{a+1}\right]:\left[\frac{1}{\sqrt{a}-1}-\frac{2\sqrt{a}}{\left(a+1\right)\left(\sqrt{a}-1\right)}\right]\)
\(M=\frac{\left(\sqrt{a}-1\right)^2}{a+1}:\left[\frac{a+1-2\sqrt{a}}{\left(\sqrt{a}-1\right)\left(a+1\right)}\right]\)
\(M=\frac{\left(\sqrt{a}-1\right)^2}{a+1}:\frac{\left(\sqrt{a}-1\right)^2}{\left(\sqrt{a}-1\right)\left(a+1\right)}\)
\(M=\frac{\left(\sqrt{a}-1\right)^2}{a+1}.\frac{\left(\sqrt{a}-1\right)\left(a+1\right)}{\left(\sqrt{a}-1\right)^2}=\sqrt{a}+1\)
\(M>1\Leftrightarrow\sqrt{a}-1>1\Leftrightarrow\sqrt{a}>2\Leftrightarrow a>4\)
\(M=\sqrt{3-2\sqrt{2}}-1\)
\(M=\sqrt{\left(\sqrt{2}-1\right)^2}-1=\sqrt{2}-1-1=\sqrt{2}-2\)
\(a,ĐKXĐ:\hept{\begin{cases}a\ge0,\sqrt{a}\ne0\\\sqrt{a}-1\ne0\\\sqrt{a}-2\ne0\end{cases}\Leftrightarrow\hept{\begin{cases}a>0\\a\ne1\\a\ne4\end{cases}}}\)
\(b,\)Rút gọn : \(Q=\left(\frac{1}{\sqrt{a}-1}-\frac{1}{\sqrt{a}}\right):\left(\frac{\sqrt{a}+1}{\sqrt{a}-2}-\frac{\sqrt{a}+2}{\sqrt{a}-1}\right)\)
\(Q=\left(\frac{\sqrt{a}}{\sqrt{a}\left(\sqrt{a}-1\right)}-\frac{\sqrt{a}-1}{\sqrt{a}\left(\sqrt{a}-1\right)}\right):\left(\frac{\left(\sqrt{a}+1\right)\left(\sqrt{a}-1\right)}{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}-\frac{\left(\sqrt{a}+2\right)\left(\sqrt{a}-2\right)}{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}\right)\)
\(Q=\frac{\sqrt{a}-\sqrt{a}+1}{\sqrt{a}\left(\sqrt{a}-1\right)}:\frac{a^2-1-a^2+4}{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}\)
\(Q=\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}:\frac{3}{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}\)
\(Q=\frac{1}{\sqrt{a}\left(\sqrt{a}-1\right)}.\frac{\left(\sqrt{a}-1\right)\left(\sqrt{a}-2\right)}{3}\)
\(Q=\frac{\sqrt{a}-2}{3\sqrt{a}}\)
c, bn thay vào rồi tính nha
\(A=\left(\frac{\sqrt{x}-1}{\sqrt{x}+1}-\frac{\sqrt{x}+1}{\sqrt{x}-1}\right)\left(\frac{1}{2\sqrt{x}}-\frac{\sqrt{x}}{2}\right)^2\)
\(\Leftrightarrow A=\left[\frac{\left(\sqrt{x}-1\right)\left(\sqrt{x}-1\right)-\left(\sqrt{x}+1\right)\left(\sqrt{x}+1\right)}{\left(\sqrt{x}+1\right)\left(\sqrt{x}-1\right)}\right]\left[\left(\frac{1}{2\sqrt{x}}\right)^2-2.\frac{1}{2\sqrt{x}}.\frac{\sqrt{x}}{2}+\left(\frac{\sqrt{x}}{2}\right)^2\right]\)
\(\Leftrightarrow A=\left[\frac{\left(\sqrt{x}-1\right)^2-\left(\sqrt{x}+1\right)^2}{x-1}\right]\left(\frac{1}{4x}-\frac{1}{2}+\frac{x}{4}\right)\)
\(\Leftrightarrow A=\left(\frac{x-2\sqrt{x}+1-x-2\sqrt{x}-1}{x-1}\right)\left(\frac{1}{4x}-\frac{2x}{4x}+\frac{x^2}{4x}\right)\)
\(\Leftrightarrow A=\frac{-4\sqrt{x}}{x-1}.\frac{\left(1-x\right)^2}{4x}\)
\(\Leftrightarrow A=\frac{4\sqrt{x}}{1-x}.\frac{\left(1-x\right)^2}{4x}\)
\(\Leftrightarrow A=\frac{1-x}{\sqrt{x}}\)
b) \(\frac{A}{\sqrt{x}}>1\)
\(\Leftrightarrow\frac{1-x}{\frac{\sqrt{x}}{\sqrt{x}}}>1\)
\(\Leftrightarrow1-x>1\Leftrightarrow x< 0\)
A= \(\sqrt{1-a}\)+\(\sqrt{a\left(a-1\right)}\)+a\(\sqrt{\frac{a-1}{a}}\)
ĐKXD: a=1 a<0
a=1 => A=0
a,=>A=\(\sqrt{1-a}\)+\(\sqrt{a\left(a-1\right)}\)+a\(\sqrt{\frac{a-1}{a}}\)
=\(\sqrt{1-a}\)+\(\sqrt{a\left(a-1\right)}\) - \(\sqrt{\frac{a^2-1}{a}}\)
=\(\sqrt{1-a}\)+\(\sqrt{\left(a-1\right)}\)-\(\sqrt{a\left(a-1\right)}\)
=\(\sqrt{1-a}\)
\(\sqrt{1-a}+\sqrt{a\left(a-1\right)}+\sqrt{\frac{a^2\left(a-1\right)}{a}}=\sqrt{1-a}+\sqrt{a\left(a-1\right)}+\sqrt{a\left(a-1\right)}=\sqrt{1-a}\left(2\sqrt{-a}+1\right)\)